2016
DOI: 10.4055/cios.2016.8.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Variability of the Shoulder between the Populations of North American and East Asian

Abstract: BackgroundThe aim of this study was to determine if there were significant differences in glenohumeral joint morphology between North American and East Asian populations that may influence sizing and selection of shoulder arthroplasty systems.MethodsComputed tomography reconstructions of 92 North American and 58 East Asian patients were used to perform 3-dimensional measurements. The proximal humeral position was normalized in all patients by aligning it with the scapular plane utilizing anatomic landmarks. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 20 publications
(35 reference statements)
3
40
1
Order By: Relevance
“…[17][18][19][20] It has also been reported that the mean glenoid height is 38.0 mm (29.4-50.1 mm), and the mean difference between men and women is 4.7 mm. [17][18][19][20] The differences between these values and the analysis results of anatomic landmarks in this study are almost similar to the disparities in the anatomic landmarks between North American and East Asian populations presented by Cabe-zas et al 21) Pinkas et al 19) noted the importance of the glenoid vault of the cancellous bone surrounded by the thin cortical bone.In this study, it was found that as glenoid height became smaller, glenoid apex range was increased, and that as glenoid width became narrower, glenoid apex range was increased. These findings suggest that even if glenoid height is large, the portion of glenoid apex where the glenoid component can be safely inserted is small, so the glenoid component should be inserted carefully.…”
Section: Discussionsupporting
confidence: 85%
“…[17][18][19][20] It has also been reported that the mean glenoid height is 38.0 mm (29.4-50.1 mm), and the mean difference between men and women is 4.7 mm. [17][18][19][20] The differences between these values and the analysis results of anatomic landmarks in this study are almost similar to the disparities in the anatomic landmarks between North American and East Asian populations presented by Cabe-zas et al 21) Pinkas et al 19) noted the importance of the glenoid vault of the cancellous bone surrounded by the thin cortical bone.In this study, it was found that as glenoid height became smaller, glenoid apex range was increased, and that as glenoid width became narrower, glenoid apex range was increased. These findings suggest that even if glenoid height is large, the portion of glenoid apex where the glenoid component can be safely inserted is small, so the glenoid component should be inserted carefully.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the lack of direct comparison, it is likely that there are few, if any, differences in glenoid thickness between Koreans and Westerners. For example, Cabezas et al 21) conducted an analysis of morphologic variability of the shoulder between the populations of North American and East Asia. They reported that the East Asian population exhibited smaller shoulder morphometrics than did the North American cohort, especially regarding the glenoid height and inferior glenoid width.…”
Section: Discussionmentioning
confidence: 99%
“…Also, higher rates of notching observed in our study as compared to other BIO-RSA studies may be because of our study population and prosthesis sizing limitation. As already quantified, the East Asian population has smaller glenoid sizes, especially females [17]. This reverse prosthesis design was not originally designed according to their morphology.…”
Section: Discussionmentioning
confidence: 99%